Laurus nobilis leaf extract controls inflammation by suppressing NLRP3 inflammasome activation. Issue 5 (1st November 2018) - Lee, Eun Hye; Shin, Jin Hak; Kim, Seon Sook; Lee, Hanbyeol; Yang, Se‐Ran; Seo, Su Ryeon
Abstract: Laurus nobilis Linn. (Lauraceae), commonly known as Bay, has been used as a traditional medicine in the Mediterranean and Europe to treat diverse immunological disorders. Although the effects of L. nobilis on immunosuppression have been reported, the detailed underlying mechanism remains unclear. In this study, to elucidate the anti‐inflammatory mechanism of L. nobilis, we examined the effect of L. nobilis leaf extract on inflammasome activation in mouse bone marrow‐derived macrophages. L. nobilis leaf extract inhibited NOD‐like receptor pyrin domain‐containing 3 (NLRP3) inflammasome activation, which was associated with caspase‐1 activation, interleukin‐1β secretion, and apoptosis‐associated speck‐like protein containing a CARD (ASC) pyroptosome complex formation. We also observed that 1, 8‐cineole, the major component of L. nobilis extract, consistently suppressed NLRP3 inflammasome activation. Furthermore, L. nobilis leaf extract attenuated the in vivo expression of proinflammatory cytokines in an acute lung injury mouse model. Our results provide the first evidence that L. nobilis leaf extract modulates inflammatory signaling by suppressing inflammasome activation. Abstract : Laurus nobilis Linn. (Lauraceae) has been used as a traditional medicine in the Mediterranean and Europe to treat diverse immunological disorders. Our results provide the first evidence that L. nobilis leaf extract modulates inflammatory signaling by suppressing NOD‐like receptor pyrin domain‐containing 3 (NLRP3) inflammasome activation.